Implementing the Merdeka Curriculum in English Language Teaching: A Study of Teacher Learning Steps - Latifa, Helmia; Ratih, Koesoemo; Maryadi, Maryadi (Universitas Hamzanwadi, 2023)
The Merdeka curriculum, a pivotal element in contemporary Indonesian education, encapsulates three key learning components: objectives, steps, and assessment. This study investigates into one of these components namely the learning steps in the context of English language instruction. Adopting a phenomenological approach, the research focuses on two English teachers at a junior high school in Central Java, aiming to illuminate the practical implementation of the learning steps. Data collection encompassed classroom observations, in-depth interviews with the teachers, and comprehensive documentation, including visual records from the classes. This multifaceted approach yielded rich qualitative insights into the pedagogical practices and experiences of these educators. The findings reveal a tripartite structure of the learning steps: the 'Opening' phase, where teachers connect new content with students' prior knowledge and motivate them towards the lesson; the 'Core Activities' phase, involving exploration, elaboration, and confirmation of the subject matter; and the 'Closing' phase, which includes summarizing key points, reflective activities, and preparing students for future lessons. Significantly, these structured phases highlight the holistic and effective methodology of the Merdeka curriculum in teaching English, offering valuable insights into its practical implementation and impact on educational outcomes.